2019
DOI: 10.1111/ctr.13571
|View full text |Cite
|
Sign up to set email alerts
|

Deceased organ donor factors influencing pancreatic graft transplantation and survival

Abstract: Criteria for organ acceptance in brain-dead organ donors remain inconsistent, especially when concerning pancreatic transplants. We sought to examine donor-specific predictors of pancreatic graft use and survival to better guide the selection and management of potential donors. A prospective observational study of all donors from ten organ procurement organizations was conducted from March 2012 to January 2015. Critical care endpoints were collected at 4 standardized time points. Data associated with pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Achieving these critical care endpoints has been associated with an increased number of organs transplanted per donor 10,19-21 as well as graft survival rates for specific organs. 22-24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving these critical care endpoints has been associated with an increased number of organs transplanted per donor 10,19-21 as well as graft survival rates for specific organs. 22-24…”
Section: Discussionmentioning
confidence: 99%
“…Achieving these critical care endpoints has been associated with an increased number of organs transplanted per donor 10,[19][20][21] as well as graft survival rates for specific organs. [22][23][24] The relationship between DBD-donor demographics, meeting DMGs, utilization of a donor liver for transplantation, and graft survival rates of livers has been studied by Bloom et al 22 The authors used prospectively collected data from 8 OPOs and after controlling for known predictors, donor BMI, male sex, normal glucose levels, the use of dopamine at the time of authorization for donation, and the use of vasopressin at time of allocation were associated with improved liver utilization. However, at follow-up, only donor BMI and serum sodium level at the time of allocation of organs were associated with improved graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, donor hyperglycemia or need for insulin therapy could be related to the physiological response to injury or administration of exogenous glucose and steroids. Consequently, these factors should not be considered a contraindication for transplantation in the absence of a donor history of diabetes 29,30 . Donor hemodynamic instability and vasopressor requirement implies inadequate perfusion and may increase the risk of graft thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, these factors should not be considered a contraindication for transplantation in the absence of a donor history of diabetes. 29,30 Donor hemodynamic instability and vasopressor requirement implies inadequate perfusion and may increase the risk of graft thrombosis. The visual inspection, texture, and consistency of the pancreas provide valuable information at the time of procurement, especially fatty infiltration, or any injury, although these findings are hard to quantify.…”
mentioning
confidence: 99%
“…This approach to critical care of the organ donor, as well as similar DMGs implemented by various institutions, has improved both the number of organs used for transplant per donor, and the quality of organs transplanted. 4,25,[28][29][30][31][32][33][34] Recently, Malinoski et al showed that, in kidney transplantation, meeting the "DMG Bundle," defined as at least seven out of nine DMGs in the deceased donor at the time of donation authorization, was associated with a lower rate of DGF in a small cohort. 4 The aim of this study was to build a comprehensive model to evaluate the association between meeting individual DMGs in deceased organ donors prior to organ recovery and the development of DGF in kidney transplant recipients.…”
mentioning
confidence: 99%